Age and Lymph Node Positivity in Patients With Colon and Rectal Cancer in the US Military Health System. Issue 3 (March 2020) - Alexander, Melannie S.; Lin, Jie; Shriver, Craig D.; McGlynn, Katherine A.; Zhu, Kangmin
Abstract : BACKGROUND: Young age may be associated with an increased risk of lymph node involvement at diagnosis of colorectal cancer. Accessibility to care, which is related to cancer detection, tumor stage, and therefore lymph node positivity, may vary by age and thus influence research results. OBJECTIVE: The purpose of this study was to investigate whether young patients had an increased risk of lymph node–positive colon and rectal cancers in the Department of Defense Military Health System, which provides universal health care to its beneficiaries. DESIGN: This was a retrospective, cross-sectional study. SETTINGS: Patients were identified from the US Department of Defense Automated Central Tumor Registry. PATIENTS: Included patients were diagnosed with histologically confirmed primary stage I to III colon and rectal adenocarcinomas between 1989 and 2013, had surgery and ≥1 lymph node examined, and did not receive preoperative radiotherapy. Logistic regression was used to examine the relationships between age at diagnosis (18–49, 50–59, 60–69, and ≥70 y) and lymph node positivity overall and stratified by tumor T stage and number of lymph nodes examined. MAIN OUTCOME MEASURES: Lymph node positivity of colon and rectal cancers was measured. RESULTS: The youngest patients (aged 18–49 y) were more likely to have lymph node–positive colon and rectal cancers compared with those who were aged ≥70 years after adjustment for potential confounders (OR = 2.04 and 95% CI, 1.63-2.56 for colon cancer; OR = 1.73 and 95% CI, 1.11-2.70 for rectal cancer). A similar tendency was shown in most colon and rectal cancer subgroups stratified by tumor T stage and number of lymph nodes examined. LIMITATIONS: This study was limited by its small sample size for certain subgroup analyses. No information on comorbidities, BMI, or other indicators of health status was available. CONCLUSIONS: In a universal healthcare system, young age was associated with increased lymph node positivity of colon and rectal cancers, suggesting that factors other than access to care may play a role in this association. See Video Abstract at http://links.lww.com/DCR/B90 . EDAD Y POSITIVIDAD DE GANGLIOS LINFÁTICOS EN PACIENTES CON CÁNCER DEL COLON Y EL RECTO EN EL SISTEMA DE SALUD MILITAR DE EE UU: ANTECEDENTES: La edad temprana puede estar asociada con un mayor riesgo de compromiso de los ganglios linfáticos en el momento del diagnóstico de cáncer colorrectal. La accesibilidad a la atención medica, que está relacionada con la detección del cáncer, el estadio del tumor y, por lo tanto, la positividad de los ganglios linfáticos, puede variar según la edad y, por lo tanto, influir en los resultados de la investigación. OBJETIVO: Investigar si los pacientes jóvenes tenían un mayor riesgo de cáncer del colon y el recto con ganglios linfáticos positivos en el Sistema de Salud Militar del Departamento de Defensa, que brinda atención médica universal a sus beneficiarios. DISEÑO: Estudio transversal retrospectivo. MARCO: Se identificaron pacientes del Registro Automático Central de Tumores del Departamento de Defensa de los Estados Unidos. PACIENTES: Fueron diagnosticados con adenocarcinomas del colon y el recto en estadio I-III confirmados histológicamente entre 1989-2013, se les realizó una cirugía y se examinaron ≥ 1 ganglio linfático, y no recibieron radioterapia preoperatoria. La regresión logística se utilizó para examinar las relaciones entre la edad al momento del diagnóstico (18-49, 50-59, 60-69 y ≥70 años) y la positividad de los ganglios linfáticos en general y fue estratificada por el estadio T tumoral y el número de ganglios linfáticos examinados. RESULTADOS PRINCIPALES MEDIDOS: Positividad de ganglios linfáticos de cáncer del colon y el recto. RESULTADOS: Los pacientes más jóvenes (18-49 años) tenían más probabilidades de tener cáncer del colon y el recto con ganglios linfáticos positivos en comparación con aquellos que tenían 70 años o más después del ajuste por posibles factores de confusión (odds ratio: 2.04, intervalo de confianza del 95%: 1.63 -2.56 para el cáncer de colon; odds ratio: 1.73, intervalo de confianza del 95%: 1.11-2.70 para el cáncer de recto). Se mostró una tendencia similar en la mayoría de los subgrupos de cáncer del colon y el recto estratificados por el estadio T tumoral y el número de ganglios linfáticos examinados. LIMITACIONES: Tamaño de muestra pequeño para ciertos análisis de subgrupos. No hay información sobre comorbilidades, índice de masa corporal u otros indicadores del estado de salud. CONCLUSIONES: En un sistema de salud universal, la edad joven se asoció con un aumento de la positividad de los ganglios linfáticos del cáncer del colon y el recto, lo que sugiere que otros factores además del acceso a la atención medica pueden desempeñar un papel en esta asociación. Consulte Video Resumen en http://links.lww.com/DCR/B90 .